High liver fibrosis scores in metabolic dysfunction-associated fatty liver disease patients are associated with adverse atrial remodeling and atrial fibrillation recurrence following catheter ablation - Decoin, Raphaël; Butruille, Laura; Defrancq, Thomas; Robert, Jordan; Destrait, Nicolas; Coisne, Augustin; Aghezzaf, Samy; Woitrain, Eloise; Gouda, Zouriatou; Schino, Sofia; Klein, Cédric; Maboudou, Patrice; et al. (Frontiers in Endocrinology, 2022)
Background A number of epidemiological studies have suggested an association between metabolic dysfunction-associated fatty liver disease (MAFLD) and the incidence of atrial fibrillation (AF). However, the pathogenesis leading to AF in the context of MAFLD remains unclear. We therefore aimed at assessing the impact of MAFLD and liver fibrosis status on left atrium (LA) structure and function. Methods Patients with a Fatty Liver Index (FLI) >60 and the presence of metabolic comorbidities were classified as MAFLD+. In MAFLD+ patients, liver fibrosis severity was defined using the non-alcoholic fatty liver disease (NAFLD) Fibrosis Score (NFS), as follows: MAFLD w/o fibrosis (NFS ≦ −1.455), MAFLD w/indeterminate fibrosis (−1.455 < NFS < 0.675), and MAFLD w/fibrosis (NFS ≧ 0.675). In the first cohort of patients undergoing AF ablation, the structural and functional impact on LA of MAFLD was assessed by LA strain analysis and endocardial voltage mapping. Histopathological assessment of atrial fibrosis was performed in the second cohort of patients undergoing cardiac surgery. Finally, the impact of MAFLD on AF recurrence following catheter ablation was assessed. Results In the AF ablation cohort (NoMAFLD n = 123; MAFLD w/o fibrosis n = 37; MAFLD indeterm. fibrosis n = 75; MAFLD w/severe fibrosis n = 10), MAFLD patients with high risk of F3–F4 liver fibrosis presented more LA low-voltage areas as compared to patients without MAFLD (16.5 [10.25; 28] vs 5.0 [1; 11] low-voltage areas p = 0.0115), impaired LA reservoir function assessed by peak left atrial longitudinal strain (19.7% ± 8% vs 8.9% ± 0.89% p = 0.0268), and increased LA volume (52.9 ± 11.7 vs 43.5 ± 18.0 ml/m2 p = 0.0168). Accordingly, among the MAFLD patients, those with a high risk of F3–F4 liver fibrosis presented a higher rate of AF recurrence during follow-up (p = 0.0179). In the cardiac surgery cohort (NoMAFLD n = 12; MAFLD w/o fibrosis n = 5; MAFLD w/fibrosis n = 3), an increase in histopathological atrial fibrosis was observed in MAFLD patients with a high risk of F3–F4 liver fibrosis (p = 0.0206 vs NoMAFLD; p = 0.0595 vs MAFLD w/o fibrosis). Conclusion In conclusion, we found that liver fibrosis scoring in MAFLD patients is associated with adverse atrial remodeling and AF recurrences following catheter ablation. The impact of the management of MAFLD on LA remodeling and AF ablation outcomes should be assessed in dedicated studies.